Author Guidelines including Example Article (Journal of Scientific Research, 2008)
Editorial policy: The Journal of Scientific Research is a peer-reviewed international journal which appears as 3 online issues (one print volume) per year. This journal is a unifying force, going across the barriers between disciplines, addressing all related topics and materials. An International Editorial Board (along with an Advisory Board) comprising of renowned academics from various fields guides our editorial policy and direction. The Journal is devoted to the publication of original research (Research paper, Review paper, Short communication) covering the following fields:Section A: Physical and Mathematical Sciences: Physics, Mathematics, Statistics, Geophysics, Computer, Environmental Science, Communications and Information technology, Engineering and related branches.Section B: Chemical and Biological Sciences: Chemistry, Biochemistry, Pharmacy, Biology, Genetics, Fisheries and related branches.The author(s) should submit an original research finding that has not been offered to any other journals for prior or simultaneous publication.Manuscript: The manuscript, which includes an abstract (not more than 200 words, 9 pt Times New Roman), should have main text typed in 10 pt Times New Roman. The sequence should be: Title, Authors name and affiliation, Abstract, Keywords, Introduction, Main texts, Acknowledgements and References. Short communication may not have heading and subheading etc but references should be listed as usual. Research Papers (not normally more than 6000 words in length) and Short communications (not more than 3000 words in length) will be considered. Details on how to structure an article, including specific information on Tables, figures and references, are available in Instructions for Typesetting JSR Manuscript Using MS-Word.How to submit:  The text of the article is to be prepared using Microsoft Word. Please submit articles online at:   www.banglajol.info/index.php/JSROnly if unable to submit onlinesend by email to Editor-in-Chief (JSR) at: jsr_editor@ru.ac.bdPublication charge: A modest publication charge of accepted articles (does not include Reprints) to defray the partial cost of journal printing is applicable for accepted articles of volume 2 and onward – authors will get notification for that at appropriate time after acceptance of their articles. The rate per page of accepted paper isCorrespondence The Editor-in-Chief (JSR)Faculty of Sciences, Rajshahi UniversityRajshahi-6205, Bangladeshe-mail: jsr_editor@ru.ac.bdTel : +880-721-750041/4115Fax: +880-721-750064 Submission Preparation ChecklistAs part of the submission process, authors are required to check off their submission's compliance with all of the following items, and submissions may be returned to authors that do not adhere to these guidelines:1. The submission has not been previously published, nor it is before another journal for consideration (or an explanation has been provided in Comments to the Editor). 2.  The file is in Microsoft Word file format. 3.  E-mails and affiliation of all co-authors have been provided in the Metadata (mandatory) while submitting manuscript.4. The text adheres to the style, fonts, font sizes in abstract, text, figures, tables and bibliographic requirements outlined in the Author Guidelines and Instructions for Typesetting JSR Manuscripts using MS Word.5.  Copyright: Submission of paper implies transfer of copyright from the authors to the Journal of Scientific Research, Faculty of Science, Rajshahi University.  © 2009 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved.DOI: 10.3329/jsr.vlil.1704